(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Overweight and obesity are defined as abnormal or excessive fat accumulation that may impair health. Body Mass Index (BMI) is a simple index for weight for height that is commonly used to classify overweight and obesity in adults. It is defined as a person’s weight in kilogram divided by the square of his height in meters (kg/m2). To estimate the prevalence of overweight and obesity among the students of Bangladesh International School and College, Mohakhali, Dhaka. Materials and methods : This descriptive cross-sectional study was conducted from July 2019 to November 2019 among purposively selected 201 students of class VI to X of Bangladesh International School, Mohakhali, Dhaka. Data were collected through face to face interview using pre-tested structured questionnaire. Data were checked for quality control and analyzed by computer by using SPSS software version 23. Results: Mean age of the students was 13.42 ± 0.38 years. Out of 201 respondents 45 from class VI, 41 from class VII, 39 from class VIII, 36 from class IX and 40 students from class X. The highest 20.9% respondents are from 14 years age. Majority (51.2%) respondents were female and rest 48.8% were Male. The overall proportion of overweight among the respondents was found to be 18.4%. Association between overweight and age, sex, class, Occupation of mothers of respondent, monthly family income, frequency of snacks and daily calorie intake, and duration of outdoor games or physical activity were found significant. Conclusion: In this study it was revealed that the prevalence of overweight among the students of selected school was 18.4%. Boys were more overweight than the girls. Higher percentage of overweight adolescent was found among the affluent families. Adolescent students who took more calorie in daily diet the prevalence of overweight was more in them. JCMCTA 2021 ; 32 (2) : 41-46